An Overview of Digital Twins Methods Applied to Lithium-Ion Batteries - Diaz-Diaz, M; Acosta-Barbosa, K; Bugueno-Olivos, V; Rajendran, S (Institute of Electrical and Electronics Engineers Inc., 2022)
The continuous monitoring of the energy storage system in electric vehicles is essential for safe operation. In particular, most electric vehicles use Lithium-ion batteries due to their power and energy density, which can introduce instability in their performance. Recently, the use of digital twins has been able to provide more information to the battery management system for real-time decision-making. This paper presents an overview of the main methods for modeling lithium-ion batteries and the identification of parameters of these models, summarizing their advantages and disadvantages. In addition, the application of the linear parameter-varying representation and their contributions are discussed. Finally, digital twin methods applied to battery management systems are described, and their main functionalities are analysed. © 2022 IEEE.
Keywords: Battery model; Digital twin; Electric vehicle; Linear parameter-varying; Lithium-ion battery